Methodologies for Agricultural Gypsum Application Recommendations in No-Tillage Systems on Tropical Sandy Soils † - de Souza, Isabela Malaquias Dalto; Borges, Wander Luis Barbosa; Juliano, Pedro Henrique Gatto [UNESP]; Modesto, Viviane Cristina [UNESP]; Girardi, Vitória Almeida Moreira [UNESP]; de Souza Júnior, Nelson Câmara [UNESP]; Ribeiro, Naiane Antunes Alves [UNESP]; Matos, Aline Marchetti Silva [UNESP]; Galindo, Fernando Shintate [UNESP]; Andreotti, Marcelo [UNESP] (MDPI, 2025)
This study aimed to evaluate which of five commonly used methodologies for agricultural gypsum application in no-tillage systems under tropical agricultural conditions is the most efficient in sandy soils. The evaluation focused on soil chemical and physical properties, nutrient movement through the soil profile, and crop productivity. Methods: Soil layers of 0–0.20 m and 0.20–0.40 m were analyzed. Data were subjected to analysis of variance, and means were compared using Student’s t-test (p < 0.05). Principal component analysis (PCA) and multivariate analysis were also performed. Results: An increase in calcium (Ca), potassium (K), and sulfur (S) contents was observed at the analyzed soil depths, along with a reduction in subsurface aluminum saturation (m%). Gypsum application also increased the dry matter yield of cover crops. Conclusions: For sandy soils under no-tillage systems with high nutrient export, aiming to improve soil fertility and aggregation, the gypsum application methodologies proposed by Caires and Guimarães or Raij and collaborators are recommended. According to multivariate analysis, these methodologies showed the best correlation with base saturation (V%), a key indicator of soil fertility. Additionally, the Caires and Guimarães method demonstrated a stronger correlation with maize productivity. However, none of the evaluated methodologies increased soybean yields.
Keywords: soil fertility; soil health; soil profile